1986
DOI: 10.1254/jjp.41.237
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Immune Responses IV. Adrenal Involvement in the Alteration of Antibody Responses in Restraint-Stressed Mice

Abstract: Abstract-We investigated the correlation between restraint stress-induced alter ation of antibody responses and adrenal hormones. Adrenalectomy (Adx) blocked both the suppression of antibody response against T cell-dependent (TD) antigen and the enhancement of that against T cell-independent (TI) antigen in stressed mice. Adx also inhibited the atrophy of both thymus and spleen caused by restraint. Pre-treatment of metyrapone, an inhibitor of adrenocortical steroid biosynthesis, had an effect that was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…However, in another study involving exposure of Swiss-Webster mice to rotation stress (10 min/h for 5 h), ADX did not influence the stressor-induced suppression of the PFC response to SRBC [86]. The discrepancy between this last finding and those cited previously [84,85] may be due to differences in the stressors used, as well as the dura tion of exposure to the stress.…”
Section: Glucocorticoids and The Hpa Axismentioning
confidence: 51%
See 1 more Smart Citation
“…However, in another study involving exposure of Swiss-Webster mice to rotation stress (10 min/h for 5 h), ADX did not influence the stressor-induced suppression of the PFC response to SRBC [86]. The discrepancy between this last finding and those cited previously [84,85] may be due to differences in the stressors used, as well as the dura tion of exposure to the stress.…”
Section: Glucocorticoids and The Hpa Axismentioning
confidence: 51%
“…Okimura et al [84] exposed ADX or sham-ADX BALB/c mice to 2 days of restraint (12 h/day), at the end of which they were immunized with SRBC. The suppressed PFC response to SRBC in sham-restrained mice was totally abrogated by ADX [84], Similarly, Bonneau et al [85] found that exposure of ADX male C57BL/6 mice to 4 days of restraint (14-16 h/day) prior to footpad inoculation with herpes simplex virus type I (HSV-1), followed by an addi tional 5 days of restraint, resulted in an abrogation of sup pressed HSV-specific cytotoxic T lymphocyte (CTL) activ ity observed in sham surgery or unoperated controls ex posed to the same restraint protocol. These findings suggest that some of the effects o f restraint on antigen-specific im mune responses in mice are mediated by adrenal-dependent mechanisms.…”
Section: Glucocorticoids and The Hpa Axismentioning
confidence: 99%
“…A wide range of immunological, endocrinological and neuronal pathways are known to mediate and modulate systemic stress responses [30, 31, 32]. Okimura et al [31], for example, reported that stress-induced production of antibody was stopped by extirpation of the suprarenal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Okimura et al [31], for example, reported that stress-induced production of antibody was stopped by extirpation of the suprarenal glands. Various studies have also revealed that plasma levels of catecholamines, corticosterone and ACTH are increased by the application of restraint stress [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Os glicocorticóides regulam uma escala de processos biológicos, tais como, proliferação de células, inflamação, imunidade e a diminuição na ativação de células natural Killer (NK) (IWAKABE et al, 1998;SAPERSTEIN et al, 1992;WU et al, 2000), supressão na fagocitose de macrófagos (LU et al, 1998), a liberação de óxido nítrico (NO) e TNF-α (AARSTAD et al, 1991;BROWN & ZWILLING, 1994;KIZAKI et al, 1996), alterando a sensibilidade do IFN-γ (ZWILLING et al, 1992), inibindo a proliferação de células T, produzindo IL-2 e IFN-γ (IWAKABE et al, 1998;LI et al,1997), modulando a expressão MHC de classe II (ZWILLING et al, 1990), efetuando o equilíbrio de células T do tipo 1 e 2 (Th1/Th2) (IWAKABE et al, 1998), e modulando a produção de anticorpos (FUKUI et al, 1997;KOMORI et al, 1996;OKIMURA et al, 1986). É bem aceitável que, a suscetibilidade à infecção e a defesa do hospedeiro contra a invasão de patógenos pode ser alterada em conseqüência aos efeitos de modulação do estresse sobre a resposta imune (BIONDI & ZANNINO, 1997;YANG & GLASER, 2000).…”
Section: Contagem De Neurônios Do Cólonunclassified